Энтропийный метод выбора технологического процесса реализации проекта - Шахов, А. В.; Бокарева, М. О. (НТУ "ХПІ", 2015)
Предлагается энтропийный метод выбора технологического процесса, обеспечивающего с наибольшей вероятностью достижение плановых показателей продукта проекта по срокам, стоимости и качеству. Применение энтропии позволяет качественнее учитывать хаотичность, сложность, неопределенность, конфликтность, альтернативность, неполноту информации и обусловленный ими экономический и управленческий риск.

Entropy method of selecting the technological process that provides most likely the achievement of product targets of the project on time, cost and quality basis is proposed in this article. Application of entropy can qualitatively take into account the randomness, complexity, uncertainty, conflict, alternatively, incomplete information and the resulting economic and management risk.
Entropy method of selecting the technological process during the fulfilment of the project
Keywords: энтропия; сетевая модель; метод стратификации; клиент; качество; entropy; network model; method of stratification